Continental geochemical signatures in dacites from Iceland and implications for models of early Archaean crust formation - Willbold, Matthias; Hegner, Ernst; Stracke, Andreas; Rocholl, Alexander (Earth and Planetary Science Letters, 2009)
ISSN:0012-821X ISSN:1385-013X